Study on Stress Distribution Law of Anchorage Body - Huang, Yingjun; Zhang, Linchao; Ren, Dahua; Wei, Sijiang (International Journal of Natural Resources and Environmental Studies, 2024)
In order to reveal the stress distribution law of the anchorage body during the drawing process, through the analysis and research on the anchoring mechanism of the anchor rod, it is found that the bonding mechanism of the interface between the anchor rod and the anchoring material is mainly determined by three factors : bonding force, mechanical interlocking and friction force. The bonding mechanism of the anchorage material-surrounding rock interface is mainly determined by two factors : bonding force and friction force. Then, the mechanical model of anchorage body is established, and the distribution equations of axial force and interfacial shear stress of anchorage body are obtained by theoretical analysis. The axial force and shear stress curves are obtained by substituting the relevant parameters. It is found that the axial force and interfacial shear stress curves are exponentially decreasing. The axial force of the bolt is approximately equal to the load applied on the bolt, and at the end of the anchorage, the axial force approaches zero.